DETERMINATION OF THE POWER INTERACTION OF THE HYDRO TURBINE GRID WITH A FLUID FLOW FOR A DOUBLE-ROTOR MICRO HYDRO POWER PLANT - M. Kalimoldayev; M. Akhmetzhanov; M. Kunelbayev (Academic Scientific Journal of Computer Science, 2019)
The problem in given article consists in definition of power interaction of a lattice of the turbine with a liquid stream. The moment on the driving wheel is equal to change of the moment of quantity of movement of a proceeding liquid. To find the moment and capacity on a driving wheel shaft, it is necessary to define kinematic parameters of the stream which is flowing round a lattice of a wheel. At calculation new the blade systems the return problem of the theory of lattices is used. The return problem consists in definition of the form of a profile under the set law of distribution of speed (pressure) on a profile contour, and as in definition of power interaction of a stream and a lattice profile. For durability calculations of water-wheels it is necessary to know the hydrodynamic forces operating on the blade of the driving wheel. Analysis and study of the peculiarities of electromagnetic calculation disk generator in static mode does not allow to evaluate the work make full disk generator. This regard, studies have been conducted dynamic mode disk generator. Studies and calculations were carried out by computer simulation using the program «Ansoft Maxwell».Us essentially new design of micro hydroelectric power station with doublerotor the hydro generator is offered.